A novel synergetic targeting strategy for glioma therapy employing borneol combination with angiopep-2-modified, DOX-loaded PAMAM dendrimer. (2nd January 2018) - Han, Shunping; Zheng, Hongyue; Lu, Yanping; Sun, Yue; Huang, Anhao; Fei, Weidong; Shi, Xiaowei; Xu, Xiuling; Li, Jingjing; Li, Fanzhu
Abstract: Glioma is the most common primary malignant brain tumour and the effect of chemotherapy is hampered by low permeability across the blood–brain-barrier (BBB). Borneol is a time-honoured 'Guide' drug in traditional Chinese medicine and has been proved to be capable of promoting free drugs into the brain efficiently, but there are still risks that free drugs, especially anti-glioma drugs, may be disassembled and metabolised before penetrating the BBB and caused the whole brain distribution. The purpose of this paper was to investigate whether borneol intervention could facilitate the BBB penetration and assist glioma treatment by combining with doxorubicin (DOX) loaded PAMAM dendrimers drug delivery system modified with Angiopep-2 (a ligand of the low-density lipoprotein receptor-related protein, which overexpress both in the BBB and gliomas). The results demonstrated that Angiopep-2 modification could actually enhance the affinity between the dendrimers and the targeting cells and finally increase the cell uptake and boost the anti-tumour ability. Borneol physical combination could further enhance the anti-tumour efficiency of this targeting drug delivery system (TDDS) after penetrating BBB. Compared with free DOX solution, this TDDS illustrated obviously sustained and pH-dependent drug release. This suggested that this synergetic strategy provided a promising way for glioma therapy.